2004
DOI: 10.1177/104990910402100514
|View full text |Cite
|
Sign up to set email alerts
|

Medical house officers’ attitudes toward vigorous analgesia, terminal sedation, and physician-assisted suicide

Abstract: In 2000, the authors surveyed 236 medical house officers in three internal medicine residency programs in Connecticut to assess attitudes toward vigorous analgesia, terminal sedation, and physician-assisted suicide. The goal was to identify associations between these attitudes and training, demographic, and religious factors. The results of the study indicated that most medical house officers supported vigorous analgesia, the majority supported terminal sedation, but only a minority supported physician-assiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Results from existing U.S.-based studies suggest that residents are hesitant to participate in MAID (1–40%), but may be supportive of their colleagues’ involvement [711]. Similarly, in Mexico, residents have expressed limited support (18–29%) for MAID [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Results from existing U.S.-based studies suggest that residents are hesitant to participate in MAID (1–40%), but may be supportive of their colleagues’ involvement [711]. Similarly, in Mexico, residents have expressed limited support (18–29%) for MAID [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…27 We are aware of a report that 89% of 53 palliative care physicians agreed that terminal sedation was sometimes necessary, 1 and we found that 66% of 236 medical house officers in Connecticut agreed that it is ethically appropriate to provide terminal sedation to treat intractable pain associated with terminal illness. 28 Given the interest that patients, their families, and professionals have in the availability of aggressive palliation for terminally ill patients with refractory symptoms, there is a need to document attitudes toward terminal sedation among physicians who care for patients at the end of life. 21 We surveyed internists to: (1) determine the frequency of physician support for terminal sedation in end of life care; (2) determine whether physicians who support terminal sedation also support physician assisted suicide, and (3) explore characteristics of physicians who support terminal sedation but not assisted suicide.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] In all, 9 of 10 US physicians endorse some religious affiliation, and more than half say their religious beliefs influence their practice of medicine. 9 Moreover, studies have consistently found that physician religiosity is associated with physicians' approaches to a variety of ethically controversial medical practices.…”
mentioning
confidence: 99%
“…Some have divided physicians only into the categories of Protestants, Catholics, Jews, and other, 7,8,10,11,[19][20][21][22][23][24][25] thus potentially missing ways that less represented religious traditions shape physicians' practice. Others have included only generalized measures of religiousness (eg, frequency of prayer, religious service attendance, the importance of religion in one's life), 21,26 which cannot account for religious traditions' varying views on suffering and death and the variety of ways in which these views are internalized.…”
mentioning
confidence: 99%